Effect of Meridian Massage combined with Swallowing Rehabilitation Training on Elderly Patients with Dysphagia after Stroke - Hui FAN; Zhongqin XU; Chunxia MA; Lei DONG; Yao ZHOU (康复学报)
Objective:To observe the effect of meridian massage combined with swallowing rehabilitation training on elderly patients with dysphagia after stroke.Methods:A total of 65 elderly patients with dysphagia after stroke who were treated in the department of geriatrics of the Affiliated Hospital of Nanjing University of Chinese Medicine from March 2019 to June 2020, which were randomly divided into the control group and the observation group, with 33 cases and 32 cases in each group respectively. The control group was given routine swallowing rehabilitation training on the basis of routine treatment and early rehabilitation exercise, mainly including swallowing organ training, ice stimulation, cough and breathing training and feeding management, once a day, six days a week, continous training for four weeks, followed up for 12 weeks after discharge. The observation group was treated with meridian massage on the basis of the control group. The patients took the sitting position and relaxed the whole body, which were treated with meridian massage by combining the point-pressing manipulation, kneading manipulation and pushing manipulation in turn. Firstly, the bilateral Fengchi acupoints and Yifeng acupoints were massaged for two minutes; then, the patient's cheek was pushed and knead with his fingers from Dicang acupoint to Jiache acupoint for three minutes, and then pushed and kneaded the Chengjiang acupoint to Lianquan acupoint on Conception Vessel for two minutes; Finally, the index finger and middle finger were placed on the hyoid bone, which was pressed towards the up and back for a few seconds. During treatment, the operator was required to use gentle manipulation, gradually exerting force, from light to heavy, repeated massage should make the patient feel local"pain", so as not to cause muscle spasm on the affected side and excessive contraction of the healthy side, one time a day, six days a week, continous treatment for four weeks. The patients were given meridian massage by the family members or caregivers after discharge, and the patients were followed up for 12 weeks. Before treatment, four weeks after treatment and 12 weeks after follow-up, the Gugging swallowing screen(GUSS)was used to assess the swallowing function; the Barthel index scale was used to evaluate the activities of daily living; the incidence of aspiration and aspiration pneumonia, successful removal rate of gastric tube and indwelling time of gastric tube were compared between the two groups.Results:Before treatment, there was no significant difference in GUSS score and Barthel score between the two groups(P>0.05).Compared with the control group, the GUSS score and Barthel score of the observation group after treatment for four weeks and follow-up for 12 weeks were significantly improved, and the difference was statistically significant(P<0.05).Compared with the control group, the success rate of gastric tube removal in the observation group after treatment for four weeks was significantly higher and the indwelling time of gastric tube was significantly shorter, the difference was statistically significant(P<0.05).There was no significant difference in the incidence of aspiration and aspiration pneumonia between the two groups(P>0.05).Conclusion:Meridian massage combined with swallowing rehabilitation training can effectively improve the success rate of gastric tube removal, shorten the indwelling time of gastric tube, and improve the swallowing function and activities of daily living of elderly patients with dysphagia after stroke.